Meningkatkan Kemampuan Membaca Pemahaman Melalui Media Mind Mapping Bagi Anak Tunarungu - Putri, Suci Rahma; Taufan, Johandri (Jurnal Penelitian Pendidikan Khusus, 2021)
This study aims to prove the effectiveness of mind mapping media in improving reading comprehension skills in answering questions in the form of 5W+1H (What, Who, Where, Why, When and How) for deaf children in class VIII at SLB N 1 Painan. This study uses an experimental research in the form of Single Subject Research (SSR) with an A-B-A design. The data analysis technique is in the form of graphic visual analysis. The results of data analysis carried out for 17 meetings, which were in three conditions, namely baseline (A1) with the acquisition of percentage results, namely: 30%, 40%, 20%, 20%, 30%. In the intervention condition (B) with the percentage gain: 70% ,60% ,80%,80%, 90%90%,90%. Finally, in the baseline condition (A2), the percentage gains are: 90%,80%,90%,90%,90%. The results of this study indicate that the ability to read comprehension increases after using mind mapping media for deaf children in class VIII at SLB N 1 Painan.